2008
DOI: 10.4314/asr.v12i1.43517
|View full text |Cite
|
Sign up to set email alerts
|

South African Corporations and post- Apartheid Expansion in Africa – creating a new regional space

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…29 25 Standard Bank recently acquired 90 per cent of Uganda Commercial Bank, while in 2007 the Industrial and Commercial Bank of China paid US$5.5 billion for a 20 per cent stake in Standard Bank, which in 2009 then secured a club loan from five Chinese banks for US$1 billion (Hall 2011b, 13). 26 See also on Shoprite in Zambia, Miller (2008); and on South African investment in the region, Miller et al (2008), and in Africa more generally, Southall (2008). 27 'In Zambia, the presence of South African supermarket management at SADC trade negotiations often outweighs that of Zambia's foreign trade contingent' (Abrahams 2009, 132).…”
Section: Farm Residence and Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…29 25 Standard Bank recently acquired 90 per cent of Uganda Commercial Bank, while in 2007 the Industrial and Commercial Bank of China paid US$5.5 billion for a 20 per cent stake in Standard Bank, which in 2009 then secured a club loan from five Chinese banks for US$1 billion (Hall 2011b, 13). 26 See also on Shoprite in Zambia, Miller (2008); and on South African investment in the region, Miller et al (2008), and in Africa more generally, Southall (2008). 27 'In Zambia, the presence of South African supermarket management at SADC trade negotiations often outweighs that of Zambia's foreign trade contingent' (Abrahams 2009, 132).…”
Section: Farm Residence and Employmentmentioning
confidence: 99%
“…See also on Shoprite in Zambia, Miller (); and on South African investment in the region, Miller et al. (), and in Africa more generally, Southall ().…”
mentioning
confidence: 99%
“…apartheid was both symptomatic of and would hasten the realization of an African supermarket revolution (Miller et al 2008). Third, dietary change led by Africa's growing middle class was providing a massive new consumer market that only supermarkets were equipped to meet.…”
Section: The Supermarket Revolution and Food Security In Namibiamentioning
confidence: 99%
“…It has been observed that South African retail companies such as Wimpy (fast food), Engen (service station), Kwikserve (mini-supermarket), Woolworths (food and clothing), Game (general merchandise) and the huge regional multinational food retailer, Shoprite-Checkers (food supermarket), are building on regional economies of scale to penetrate regional markets with a host of new consumer goods and services sourced primarily from South Africa (Miller, 2008;Miller, Saunders and Oloyede, 2008;SARB, 2012).…”
Section: South Africa-originated Mncs and The Sadc Economymentioning
confidence: 99%